2010
DOI: 10.1186/1756-0500-3-193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of autolysis on the specificity of bovine spongiform encephalopathy rapid tests

Abstract: BackgroundRoutine rapid testing for Bovine Spongiform Encephalopathy (BSE) has highlighted some problems with BSE rapid test performance, the most significant being the number of initially reactive samples and the false positive results on autolyzed tissue. This point is important for BSE active surveillance in risk populations, because tissue autolysis is often unavoidable in routine cases. A robust test suitable for use on field material is therefore needed. To date, very limited information regarding the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The index herd (the herd of residence of the case animal at time of diagnosis) was visited by DAFM staff to examine the farm, herd movement records and farm records. The field investigation began once a positive screening test result was received, noting the high specificity of these tests 43 . The likely infection window (encompassing the most likely period of infection of the case animal) was determined to be 2010, the year of birth.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The index herd (the herd of residence of the case animal at time of diagnosis) was visited by DAFM staff to examine the farm, herd movement records and farm records. The field investigation began once a positive screening test result was received, noting the high specificity of these tests 43 . The likely infection window (encompassing the most likely period of infection of the case animal) was determined to be 2010, the year of birth.…”
Section: Methodsmentioning
confidence: 99%
“…The field investigation began once a positive screening test result was received, noting the high specificity of these tests. 43 The likely infection window (encompassing the most likely period of infection of the case animal) was determined to be 2010, the year of birth. The case animal was born and died in the index herd.…”
Section: Application Of the Epidemiological Framework And Bse Investimentioning
confidence: 99%
“…While correct sampling is important, tissue quality seems to be less important. If sampled tissues are autolyzed, they can still be taken and tested, which is important in any surveillance or diagnostic program [ 99 , 100 ]. In field conditions, brainstem samples are often autolyzed and contaminated with bacteria and other debris (feces, soil, hair).…”
Section: Eu-approved Rapid Testsmentioning
confidence: 99%
“…Obviously, these factors have an impact on the quality of the sample and affect the performance of the diagnostic test and the results generated [ 88 ]. Meloni et al revealed that four rapid tests (Enfer TSE Kit, Bio-Rad TeSeE test, Prionics ® -Check-LIA test, and IDEXX HerdCheck BSE Antigen Test Kit EIA) can be considered as well-running diagnostics tools regardless of tissue quality [ 100 ]. Wear et al revealed that three rapid tests (Prionics ® -Check Western blot, Platelia, and Enfer) also were able to detect PrP Sc in autolyzed tissues.…”
Section: Eu-approved Rapid Testsmentioning
confidence: 99%